If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(x-5)/9=-3
We move all terms to the left:
(x-5)/9-(-3)=0
We add all the numbers together, and all the variables
(x-5)/9+3=0
We multiply all the terms by the denominator
(x-5)+3*9=0
We add all the numbers together, and all the variables
(x-5)+27=0
We get rid of parentheses
x-5+27=0
We add all the numbers together, and all the variables
x+22=0
We move all terms containing x to the left, all other terms to the right
x=-22
| -u/4=-45 | | 6(w–97)=-36 | | (10x-5)-(3x+2)=75 | | 75=3x+4x-9 | | 5x+12-7x=-3(5x+8) | | 5m-10=275 | | 3x+17x-7=4(5x+7) | | -15+7+17y=2y+70 | | 12x+11=27 | | 1/2(x+4)-11/2X=-5 | | -8t+9=-5t–10–8 | | -9+x/8=-4x-8/7 | | 19x-7=12x-28 | | -10+7b+5=-5+9b | | (x/2)+(5/5)=2x/3 | | 2m+4/8=m | | 102/3=r+121/6 | | (14x+1)+(5x-7)=89 | | 65x-15-9x=11+56x-26 | | -4(5-7x)-(1-x)=4(x-3) | | 2x+65+25=x | | .8x+1.6x-3.2=-12.8 | | 1.5p=1.2(p+6.4) | | 3(2x+7)=14x+5-8x+16 | | -5=1/2(x | | 2x2-54=12x | | -9=-5x+4x-5 | | a-32+55a=a(2a-8)-a2+39 | | 3x+15-10x-16=3x-x-17 | | 3/2x=4/x+1/4 | | 1–m=6–6m | | 3(2)+15-10(2)-16=3x-x-17 |